Active energy ray curable resin composition, cured product thereof and laminate
By blending urethane (meth)acrylate and other components into an active energy ray-curable resin, the composition addresses the issues of moisture resistance and smoothness in undercoat layers, enhancing the durability and appearance of metallized laminates in electronics and home appliances.
Patent Information
- Application Number
- JP2020063902
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-31
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-03-31
AI Technical Summary
Existing undercoat layers in metallized laminates have insufficient moisture resistance and smoothness, which affects the durability and appearance of decorative items in electronics and home appliances.
Incorporating urethane (meth)acrylate into an active energy ray-curable resin composition, specifically blending components like urethane (meth)acrylate, monomers with (meth)acryloyl groups, (co)polymers of vinyl monomers, and a photopolymerization initiator, to enhance the smoothness and moisture resistance of the cured coating film.
The composition forms a cured coating film with excellent moisture resistance and smoothness, suitable for undercoat and topcoat layers, ensuring durability and aesthetic quality in metallized laminates.
Smart Images

Figure 0007615538000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable resin composition, and more particularly to an active energy ray-curable resin composition for forming a coating layer having excellent smoothness and moisture resistance and suitable for an undercoat layer and a topcoat layer in a metallization treatment. [Background technology]
[0002] Laminates formed by forming an undercoat layer (primer layer) on the surface of a plastic molded product, forming a metal film on top of that by a metallization process such as ionization deposition or sputtering, and then forming a topcoat layer on top of that, are extremely widely used in fields such as decorative items and home appliances.
[0003] For example, Patent Documents 1 and 2 describe a method in which a coating film of an active energy ray-curable resin composition is irradiated with active energy rays to cure it, thereby forming an undercoat layer for metallization treatment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-87274 A [Patent Document 2] JP 2012-77273 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the undercoat layers described in Patent Documents 1 and 2 have a problem in that they have insufficient moisture resistance.
[0006] An object of the present invention is to provide an active energy ray-curable resin composition capable of forming a cured coating film having excellent moisture resistance and excellent smoothness required for an undercoat layer, a topcoat layer, etc., a cured product of the composition, and a laminate having a cured coating film made of the cured product on the surface of a substrate. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered that by blending a specific urethane (meth)acrylate with an active energy ray-curable resin composition, the smoothness and moisture resistance of the resulting cured coating film can be improved, thereby arriving at the present invention.
[0008] The present invention relates to the following [1] to [9].
[0009] [1] An active energy ray-curable resin composition comprising: a urethane (meth)acrylate (A) having a structure derived from the following compound (a1); a monomer (B) other than the component (A) having at least one (meth)acryloyl group; a (co)polymer (C) of a vinyl-based monomer; and a photopolymerization initiator (D). Compound (a1): The following compound thing( a12) at least one polyol R transformation Compound (a12): Sebasin Polyester polyols obtained from acids and polyols R [2] The active energy ray-curable resin composition according to [1], wherein the urethane (meth)acrylate (A) is a urethane (meth)acrylate obtained by reacting the compound (a1), the following compound (a2), and the following compound (a3): Compound (a2): Isocyanate having at least two isocyanate groups Compound (a3): A compound having a hydroxyl group and a (meth)acryloyloxy group
[0012] [ 3]The composition [1] in which the component (A) is 5 to 50 mass%, the component (B) is 20 to 80 mass%, and the component (C) is 1 to 30 mass% based on the total amount of the components (A) to (C). or [ 2 ] To The active energy ray-curable resin composition according to claim 1, [ 4 ]The above [1]~[ 3 13. A cured product obtained by curing the active energy ray-curable resin composition according to any one of claims 1 to 12 through irradiation with active energy rays. [ 5 ] on the surface of the substrate 4 13. A laminate having a cured coating film comprising the cured product according to claim 12. [ 6 ] substrate, the above [ 4 ] and a metal film are laminated in this order. 5 ] A laminate according to the present invention. [ 7 ] The above-mentioned [ 6 ] A laminate according to the present invention. Effect of the Invention
[0013] The present invention can provide an active energy ray-curable resin composition capable of forming a cured coating film having excellent moisture resistance and excellent smoothness required for an undercoat layer, a topcoat layer, etc., a cured product of the composition, and a laminate having a cured coating film made of the cured product on the surface of a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. In this specification, "(meth)acrylate" means "acrylate" and / or "methacrylate", "(meth)acrylic" means "acrylic" and / or "methacrylic", "(meth)acryloyl" means "acryloyl" and / or "methacryloyl", "(meth)acrylonitrile" means "acrylonitrile" and / or "methacrylonitrile", and "(co)polymerization" means "homopolymerization" and / or "copolymerization". [Active energy ray curable resin composition] The active energy ray-curable resin composition of the present invention (hereinafter referred to as the present composition) is an active energy ray-curable resin composition containing a urethane (meth)acrylate (A) having a structure derived from compound (a1) described below [referred to as component (A)], a monomer (B) other than component (A) having at least one (meth)acryloyl group [referred to as component (B)], an oligomer (C) consisting of a (co)polymer of a vinyl monomer and / or a polyol other than component (A) [referred to as component (C)], and a photopolymerization initiator (D) [referred to as component (D)].
[0015] [Component (A)] The component (A) blended in the present composition is a urethane (meth)acrylate having a structure derived from the compound (a1). Examples of the component (A) include a urethane (meth)acrylate obtained by reacting the compound (a1), the compound (a2) and the compound (a3) described below, and a urethane (meth)acrylate obtained by reacting the compound (a1) and the compound (a4) described below. The component (A) contributes to the smoothness of the cured coating film obtained by curing the present composition (hereinafter simply referred to as the cured coating film).
[0016] [Compound (a1)] Compound (a1) is a polyol represented by the following compound (a11) or compound (a12). Compound (a1) contributes to the cissing resistance and smoothness of the coating film. In the synthesis of component (A), one type of polyol can be used alone as compound (a1), or two or more types can be used in combination.
[0017] [Compound (a11)] Compound (a11) is a glyceride of a fatty acid having 4 to 24 carbon atoms and a hydroxyl group. Examples of compound (a11) include castor oil, dehydrated castor oil, soybean oil having a hydroxyl group introduced therein, rapeseed oil having a hydroxyl group introduced therein, palm oil having a hydroxyl group introduced therein, and rapeseed oil having a hydroxyl group introduced therein. Among these, castor oil and dehydrated castor oil are preferred because they do not require a hydroxyl group introduction operation. When compound (a11) is used as a raw material for component (A), component (A) contains, as a structure derived from compound (a11), a structure in which at least two hydroxyl groups have been removed from a glyceride of a fatty acid having 4 to 24 carbon atoms and having hydroxyl groups.
[0018] [Compound (a12)] The compound (a12) is a polyester polyol obtained from an aliphatic polycarboxylic acid having 2 to 22 carbon atoms and a polyhydric alcohol.
[0019] Examples of the aliphatic polyvalent carboxylic acid having 2 to 22 carbon atoms used as a raw material for compound (a12) include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, aconitic acid, trimesic acid, and butanetetracarboxylic acid. Among these, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid are preferred because they facilitate control of the molecular weight of the polyester polyol.
[0020] Examples of polyols used as a raw material for compound (a12) include neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol. When compound (a12) is used as a raw material for component (A), component (A) contains, as a structure derived from compound (a12), a structure in which at least two hydroxyl groups have been removed from a polyester polyol obtained from an aliphatic polycarboxylic acid having 2 to 22 carbon atoms and a polyhydric alcohol.
[0021] In the synthesis of component (A), in addition to compound (a1), other polyols can also be used in combination as the raw polyol. Examples of other polyols include polyols such as neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol; polyether-modified polyols obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to these polyhydric alcohols; and polyols obtained by adding alkylene oxides such as ε-caprolactone, γ-butyrolactone, γ-valerolactone, and δ-valerolactone to these polyhydric alcohols. Examples of the polycaprolactone polyols include polycaprolactone polyols obtained by reacting these polyhydric alcohols and polybasic acids with lactones such as ε-caprolactone, γ-butyrolactone, γ-valerolactone, and δ-valerolactone; polycarbonate diols obtained by transesterification of diols such as 1,6-hexanediol, 3-methylpentanediol, 2,4-diethylpentanediol, trimethylhexanediol, 1,4-butanediol, 1,5-pentanediol, and 1,4-cyclohexanediol with carbonates such as ethylene carbonate, dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, and diphenyl carbonate; and polybutadiene glycol.Among these, polyols such as neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, 1,10-decanediol, 3-methylpentanediol, 2,4-diethylpentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, cyclohexanediol, hydrogenated bisphenol A, trimethylolpropane, and pentaerythritol are preferred because they provide good curing properties for the composition.
[0022] [Compound (a2)] The compound (a2) is an isocyanate having at least two isocyanate groups. The compound (a2) contributes to the flexibility of the coating film.
[0023] As the compound (a2), for example, those that have been conventionally used for the production of urethane (meth)acrylates can be used. As the compound (a2), for example, aromatic polyisocyanates such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, etc.; ethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4 ... Examples of the polyisocyanates include aliphatic polyisocyanates such as ethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, and methylcyclohexylene diisocyanate; aromatic aliphatic polyisocyanates such as xylylene diisocyanate and tetramethylxylylene diisocyanate; and biuret and allophanate forms of these polyisocyanates.
[0024] Among these, aliphatic skeleton diisocyanates such as 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,4-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate isophorone diisocyanate, bis(4-isocyanatocyclohexyl)methane, 1,2-hydrogenated xylylene diisocyanate, 1,4-hydrogenated xylylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, norbornane diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and 2,2,4-trimethylhexamethylene diisocyanate are preferred because they can impart excellent toughness to the coating film.
[0025] In the synthesis of component (A), one type of compound can be used alone as compound (a2), or two or more types of compounds can be used in combination.
[0026] [Compound (a3)] Compound (a3) is a compound having a hydroxyl group and a (meth)acryloyloxy group. Compound (a3) may be any compound as long as its hydroxyl group forms a urethane bond with the isocyanate group of compound (a1) or an intermediate compound having an isocyanate group obtained from compound (a1) and can introduce a (meth)acryloyloxy group into component (A).
[0027] Examples of the compound (a3) include (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, cyclohexane dimethanol mono (meth)acrylate, trimethylolpropane di (meth)acrylate, and pentaerythritol tri (meth)acrylate, as well as caprolactone adducts of these (meth)acrylates. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred because they provide a component (A) with a low viscosity. In synthesizing the component (A), one type of compound can be used alone as the compound (a3), or two or more types can be used in combination.
[0028] [Compound (a4)] Compound (a4) is a compound having an isocyanate group and a (meth)acryloyloxy group. Compound (a4) may be any compound as long as its isocyanate group forms a urethane bond with the hydroxyl group of compound (a1) and the (meth)acryloyloxy group can be introduced into component (A).
[0029] Examples of the compound (a4) include a compound in which a hydroxyl group of hydroxyethyl acrylate is added to the isocyanate group at the 1-position of isophorone diisocyanate, and 2-acryloyloxyethyl isocyanate having an isocyanate group at the end. Among these, from the viewpoint of toughness of the coating film, a compound in which a hydroxyl group of hydroxyethyl acrylate is added to the isocyanate group at the 1-position of isophorone diisocyanate is preferred. In synthesizing the component (A), one type of compound can be used alone as the compound (a4), or two or more types can be used in combination.
[0030] [Synthesis method of component (A)] The synthesis method of component (A) can be, for example, a conventionally known urethane (meth)acrylate synthesis method. As a specific synthesis method, for example, 2 moles of compound (a2) are charged in a flask, and a known catalyst such as dibutyltin dilaurate is further mixed. While maintaining the temperature in the flask at 40 to 80°C, 1 mole of compound (a1) is dropped using a dropping funnel to obtain a urethane prepolymer having an isocyanate group at the end. Thereafter, compound (a3) having an equivalent amount of hydroxyl group to the isocyanate group remaining at the end of the obtained urethane prepolymer is dropped, and the isocyanate group of the urethane prepolymer and the hydroxyl group of compound (a3) are added at 60 to 85°C to synthesize component (A). The end point of the reaction can be determined by quantifying the remaining isocyanate group. The reaction rate at the end point is preferably 97% or more, more preferably 99% or more. Also, component (A) can be synthesized, for example, by charging 2 moles of compound (a4) and 1 mole of compound (a1) in a flask, further mixing in a known catalyst such as dibutyltin dilaurate, and carrying out a urethane reaction between the isocyanate group of compound (a4) and the hydroxyl group of compound (a1) while maintaining the temperature in the flask at 40 to 80°C. The end point of the reaction can be determined by quantifying the remaining isocyanate groups. The reaction rate at the end point is preferably 97% or more, more preferably 99% or more.
[0031] [Mixing ratio of component (A)] The blending ratio of component (A) in the present composition is preferably 5 to 50 mass %, more preferably 10 to 40 mass %, based on the total amount of components (A), (B) and (C). The higher the blending ratio of component (A), the more improved the smoothness and cissing resistance of the cured coating film, and the lower the blending ratio, the more improved the adhesion to the metal film tends to be.
[0032] [Component (B)] Component (B) is a monomer having at least one (meth)acryloyl group other than component (A). Component (B) may be appropriately selected depending on the performance required of the cured coating film.
[0033] Examples of monomers having one (meth)acryloyl group that can be used as component (B) include (meth)acrylates having a hydroxyl group-containing hydrocarbon skeleton, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (meth)acrylates having a hydrocarbon group, such as 2-ethyl-hexyl (meth)acrylate, lauryl (meth)acrylate, and 2-isobutyl-2-methylacrylate; tetrahydrofurfuryl (meth)acrylate, 2-ethyl-2-methyl-1,3-dioxolan-4-yl-methyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, adamantyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, and dicyclopentenyl (meth)acrylate. (meth)acrylates having a ring skeleton, such as tert-butylcyclohexyloxyethyl (meth)acrylate, isobornyloxyethyl (meth)acrylate, norbornyloxyethyl (meth)acrylate, and adamantyloxyethyl (meth)acrylate;Examples of the (meth)acrylates include alkoxy group-containing hydrocarbon skeletons such as 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, methoxydibutylene glycol (meth)acrylate, methoxytributylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxytriethylene glycol (meth)acrylate, ethoxydipropylene glycol (meth)acrylate, ethoxytripropylene glycol (meth)acrylate, ethoxydibutylene glycol (meth)acrylate, ethoxytributylene glycol (meth)acrylate, and butoxyethyl (meth)acrylate; (meth)acrylamides such as dimethylacrylamide; and (meth)acrylamides having heterocycles such as acryloylmorpholine.
[0034] Examples of monomers having two (meth)acryloyl groups that can be used as component (B) include di(meth)acrylates having a ring skeleton such as tricyclodecane dimethanol di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, and bisphenoxyfluorene ethanol di(meth)acrylate; di(meth)acrylates having an isocyanuric acid skeleton such as bis(2-acryloyloxyethyl)-2-hydroxyethyl isocyanurate; di(meth)acrylates having a trimethylolpropane skeleton such as neopentyl glycol modified trimethylolpropane di(meth)acrylate; 1,4-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 3-methyl-1,5-pentanediol di(meth)acrylate. , 2,4-diethyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,11-undecanediol di(meth)acrylate, di(meth)acrylates having a hydrocarbon skeleton, such as 1,12-dodecanediol di(meth)acrylate, 1,13-tridecanediol di(meth)acrylate, and 1,14-tetradecanediol di(meth)acrylate; and di(meth)acrylates having a polyether skeleton, such as tripropylene glycol di(meth)acrylate and polybutylene glycol di(meth)acrylate.
[0035] Examples of monomers having three (meth)acryloyl groups that can be used as component (B) include tri(meth)acrylates having a pentaerythritol skeleton, such as pentaerythritol tri(meth)acrylate and ethoxylated pentaerythritol tri(meth)acrylate; tri(meth)acrylates having a trimethylolpropane skeleton, such as trimethylolpropane tri(meth)acrylate and tris-ethoxylated trimethylolpropane tri(meth)acrylate; and tri(meth)acrylates having an isocyanuric acid skeleton, such as tris(2-acryloyloxyethyl)isocyanurate.
[0036] Examples of monomers having four or more (meth)acryloyl groups that can be used as component (B) include poly(meth)acrylates having a pentaerythritol skeleton, such as dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated pentaerythritol tetra(meth)acrylate; and poly(meth)acrylates having a trimethylolpropane skeleton, such as ditrimethylolpropane tetra(meth)acrylate.
[0037] Examples of epoxy poly(meth)acrylates that can be used as component (B) include bisphenol-type epoxy di(meth)acrylates and novolac-type epoxy di(meth)acrylates.
[0038] Examples of polyester poly(meth)acrylates that can be used as component (B) include compounds obtained by reacting polyester polyols obtained by esterification reaction of polybasic acids such as phthalic acid, succinic acid, hexahydrophthalic acid, tetrahydrophthalic acid, terephthalic acid, azelaic acid, and adipic acid with polyols such as ethylene glycol, hexanediol, polyethylene glycol, and polytetramethylene glycol with (meth)acrylic acid or a derivative thereof.
[0039] As component (B), a urethane (meth)acrylate other than component (A) can also be used. Examples of such urethane (meth)acrylates include a compound synthesized from compound (a2) and compound (a3), a polyol other than compound (a1), and a compound obtained by reacting compound (a2) and compound (a3).
[0040] As component (B), one type of compound can be used alone, or two or more types can be used in combination.
[0041] [Bulk Proportion of Component (B)] The blending ratio of component (B) is preferably 20 to 80 mass %, more preferably 25 to 75 mass %, based on the total amount of components (A), (B) and (C). The more component (B) is added, the more improved the curability is, and the less component (B) is added, the more improved the adhesion between the cured coating film and the metal film tends to be.
[0042] [Component (C)] Component (C) is a (co)polymer of a vinyl monomer. Examples of a method for producing component (C) include a method of polymerizing one or more vinyl monomers in the presence of a conventionally known radical polymerization initiator by a solution polymerization method, a bulk polymerization method, an emulsion polymerization method, or the like.
[0043] Examples of vinyl monomers that can be used as raw materials for component (C) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, 2-dicyclohexyl (meth)acrylate, and the like. (Meth)acrylates not containing a hydroxyl group, such as tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2 ... hydroxyalkyl (meth)acrylates such as (meth)acrylate and 4-hydroxybutyl (meth)acrylate; hydroxyl group-containing vinyl monomers such as adducts of 2-hydroxyethyl (meth)acrylate and alkylene oxide or organic lactone, such as an adduct of 2-hydroxyethyl (meth)acrylate and ethylene oxide, an adduct of 2-hydroxyethyl (meth)acrylate and propylene oxide, and an adduct of 2-hydroxyethyl (meth)acrylate and ε-caprolactone; styrene or styrene derivatives such as styrene, α-methylstyrene, pt-butylstyrene, and vinyltoluene; acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, maleic acid, and fumaric acid; unsaturated nitriles such as (meth)acrylonitrile; unsaturated carboxylic acid esters such as diethyl maleate, dibutyl maleate, dibutyl fumarate, diethyl itaconate, and dibutyl itaconate; and vinyl esters such as vinyl acetate and vinyl propionate.
[0044] As the component (C), one type of (co)polymer can be used alone, or two or more types of (co)polymers can be used in combination.
[0045] [Composition ratio of component (C)] The blending ratio of component (C) is preferably 1 to 30 mass %, and more preferably 10 to 30 mass %, based on the total amount of components (A), (B) and (C). The higher the blending ratio of component (C), the better the adhesion of the cured coating film to the metal film, and the lower the blending ratio, the better the smoothness of the cured coating film tends to be.
[0046] [Component (D)] Component (D) is a photopolymerization initiator that cures the composition by irradiation with active energy rays. Examples of component (D) include benzophenone-type, anthraquinone-type, alkylphenone-type, thioxanthone-type, acylphosphine oxide-type, and phenylglyoxylate-type photopolymerization initiators.
[0047] Examples of the component (D) include benzophenone-type compounds such as benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl orthobenzoylbenzoate, and 4-phenylbenzophenone; anthraquinone-type compounds such as t-butylanthraquinone and 2-ethylanthraquinone; 2-hydroxy-2-methyl-1-phenylpropan-1-one, oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone}, benzyl dimethyl ketal, 1-hydroxycyclohexyl phenyl ketone, benzoin methyl ether, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylprop alkylphenone type such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, diethylthioxanthone, and isopropylthioxanthone; acylphosphine oxide type such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; and phenylglyoxylate type photopolymerization initiators such as phenylglyoxylic acid methyl ester.
[0048] Among these, benzophenone, 2-ethylanthraquinone, 1-hydroxycyclohexyl phenyl ketone, and 2,2-dimethoxy-1,2-diphenylethan-1-one are preferred from the viewpoint of dryness to the touch of the present composition.
[0049] As component (D), one type of compound can be used alone, or two or more types can be used in combination.
[0050] [Amount of component (D)] The amount of component (D) is preferably 0.1 to 15 parts by mass, and more preferably 1 to 10 parts by mass, per 100 parts by mass of the total amount of components (A), (B) and (C). The greater the amount of component (D), the better the curability of the composition in an air atmosphere, while the smaller the amount of component (D) tends to be, the less the amount of component (D) remaining in the cured coating film.
[0051] [Photosensitizer] The composition may contain a photosensitizer as needed, such as known photosensitizers such as methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, amyl 4-dimethylaminobenzoate, and 4-dimethylaminoacetophenone.
[0052] [Organic solvents] The composition may contain an organic solvent as necessary for adjusting the viscosity, etc. Examples of the organic solvent include ketone compounds such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester compounds such as methyl acetate, ethyl acetate, butyl acetate, ethyl lactate, and methoxyethyl acetate; ether compounds such as diethyl ether, ethylene glycol dimethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, and dioxane; aromatic compounds such as toluene and xylene; aliphatic compounds such as pentane, hexane, and petroleum naphtha; alcohol compounds such as isopropyl alcohol, isobutanol, and n-butanol; and propylene glycol compounds such as 1-methoxypropanol and 1-methoxypropanol acetate.
[0053] [Other ingredients] The composition may contain additives such as leveling agents, antifoaming agents, antisettling agents, lubricants, abrasives, rust inhibitors, antistatic agents, light stabilizers, ultraviolet absorbers, and polymerization inhibitors.
[0054] Furthermore, resins other than component (C), such as alkyd resins, may be blended within the range that does not impair the effects of the present invention.
[0055] [Laminate] The laminate of the present invention is a laminate having a cured coating film formed of a cured product obtained by irradiating the present composition with active energy rays and curing the composition on the surface of a substrate. The present composition can be suitably used as a material for an undercoat layer to be formed on the surface of a substrate in advance when a metal film is formed on the surface of the substrate by metallization treatment such as deposition or sputtering. The substrate is preferably a molded product made of resin. Examples of the molded product include molded products made of resins such as ABS resin, AES resin, polycarbonate, acrylic resin, polystyrene, etc.; polyolefins such as polypropylene and polyethylene; and polyesters such as PET and PBT. The present composition is suitable as a material for an undercoat layer in the metallization treatment of molded products that require excellent appearance, such as cosmetic containers and housings for home appliances made of ABS resin, polycarbonate, and acrylic resin. A laminate in which the above-mentioned substrate, the cured coating film (undercoat layer) made of the cured product of the present composition, and the metal film are laminated in this order is a preferred example of the laminate of the present invention.
[0056] To form an undercoat layer on a substrate, the composition is applied to the surface of the substrate and then irradiated with active energy rays. The thickness of the undercoat layer is preferably in the range of 3 to 40 μm.
[0057] The present composition can also be used as a topcoat layer to be laminated on the surface of a metal film formed by a metallization process such as vapor deposition, sputtering, etc. In this case, the undercoat layer of the metal film does not need to be formed from the present composition, but as described above, the undercoat layer formed from the present composition has good moisture resistance and smoothness, so it is preferable that it is formed from the present composition. To form a topcoat layer on a metal film, the composition is applied to the surface of the metal film and then irradiated with active energy rays. The thickness of the topcoat layer is preferably in the range of 3 to 40 μm.
[0058] Examples of methods for applying the present composition include brush coating, spray coating, dip coating, spin coating, and flow coating. From the viewpoints of workability in application and smoothness and uniformity of the cured coating film, spray coating and flow coating are preferred.
[0059] When the composition contains an organic solvent, it is preferable to volatilize the organic solvent before curing the applied composition by irradiating it with active energy rays. In this case, it is preferable to heat the composition with an IR heater or hot air at 30 to 70°C for 2 to 8 minutes to volatilize the organic solvent.
[0060] Examples of active energy rays used to cure the composition include ultraviolet rays, electron beams, etc. For example, when ultraviolet rays are irradiated using a high-pressure mercury lamp, the amount of energy is 100 to 5000 mJ / cm. 2 is preferable, and 500 to 2000 mJ / cm 2 is more preferred.
[0061] To form a metal film on the undercoat layer, which is a cured coating film of the present composition, known metallization methods such as vapor deposition and sputtering can be used. EXAMPLES
[0062] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are based on mass.
[0063] As the compound (a1), the following polyol was prepared. "SE-2003": Sebacic acid / 1,3-propanediol polyester polyol (hydroxyl value 57.7 mg KOH / g) manufactured by Ito Oil Mills [corresponding to compound (a12)] "ELA-DR": Toyokuni Oil Mills, castor oil (hydroxyl value 161.0 mg KOH / g) [corresponding to compound (a11)]
[0064] [Synthesis Example 1] Production of urethane acrylate (UA-1) In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 152.3 parts of isophorone diisocyanate (hereinafter referred to as IPDI) as compound (a2), 666.2 parts of "SE-2003" as compound (a12), and 0.04 parts of dibutyltin dilaurate (DBTL) as a reaction catalyst were added and reacted at 70°C. When the residual isocyanate group reached 3.6% or less, 81.5 parts of 2-hydroxyethyl acrylate (HEA) as compound (a3), 0.05 parts of 2,6-di-tert-butylcresol (BHT) as a polymerization inhibitor, and 0.40 parts of 4-methoxyphenol (MEHQ) were added and reacted at 70°C. When the residual isocyanate group reached 0.1% or less, the reaction was terminated to produce urethane acrylate UA-1, which is component (A).
[0065] [Synthesis Example 2] Production of urethane acrylate (UA-2) Urethane acrylate UA-2, which is component (A), was produced in the same manner as in Synthesis Example 1, except that compound (a3) was changed to 101.2 parts of 4-hydroxybutyl acrylate (4-HBA).
[0066] [Synthesis Example 3] Production of urethane acrylate (UA-3) In a flask equipped with an internal thermometer, a stirrer, and a cooling tube, 468.0 parts of VESTANAT (registered trademark) EP-DC 1241 (manufactured by EVONIK, a compound in which a hydroxyl group of hydroxyethyl acrylate is added to the isocyanate group at the 1st position of IPDI) as compound (a4), 482.0 parts of "ELA-DR" as compound (a11), 0.08 parts of dibutyltin dilaurate (DBTL) as a reaction catalyst, 0.05 parts of 2,6-di-tert-butylcresol (BHT) as a polymerization inhibitor, and 0.38 parts of 4-methoxyphenol (MEHQ) were added and reacted at 70 ° C. The reaction was terminated when the remaining isocyanate group became 0.1% or less, and urethane acrylate UA-3, which is component (A), was produced.
[0067] [Synthesis Example 4] Production of copolymer (PA-1) 500g of toluene was charged into a 2L four-neck flask and heated to an internal temperature of 80°C. Next, a mixture of 125g (25% by mass) of N-(n-butoxymethyl)acrylamide, 200g (40% by mass) of methyl methacrylate, 175g (35% by mass) of styrene, and 1g of azobisisobutylnitrile as a polymerization catalyst was dripped into the flask at a constant rate for 2 hours. The dripping was performed while stirring the flask and maintaining the internal temperature at 80°C. After that, 0.2g of azobisisobutylnitrile was added every hour for a total of four times while stirring at 80°C for 6 hours to produce copolymer PA-1, which is component (C). The weight average molecular weight of PA-1 measured by GPC in terms of polystyrene was 2.5 x 10 4 It was.
[0068] [Synthesis Example 5] Production of copolymer (PA-2) A copolymer PA-2, which is component (C), was produced in the same manner as in Synthesis Example 4, except that the mixing ratio of the monomers to be dropped was 120 g (24 mass%) of N-(n-butoxymethyl)acrylamide, 100 g (20 mass%) of methyl methacrylate, 170 g (34 mass%) of styrene, and 110 g (22 mass%) of isobornyl methacrylate. The weight average molecular weight of PA-2 measured by GPC in terms of polystyrene was 1.7 × 10 4 It was.
[0069] [Synthesis Example 6] Production of copolymer (PA-3) A copolymer PA-3, which is component (C), was produced in the same manner as in Synthesis Example 4, except that the mixing ratio of the monomers to be dropped was 275 g (55 mass%) of methyl methacrylate, 115 g (23 mass%) of isobornyl methacrylate, and 110 g (22 mass%) of FA-513M. The weight average molecular weight of PA-3 measured by GPC in terms of polystyrene was 5.9 × 10 4 It was.
[0070] [Synthesis Example 7] Production of copolymer (PA-4) A copolymer PA-4, which is component (C), was produced in the same manner as in Synthesis Example 4, except that the mixing ratio of the monomers to be dropped was 150 g (30 mass%) of N-(n-butoxymethyl)acrylamide, 25 g (5 mass%) of methyl methacrylate, 250 g (50 mass%) of isobornyl methacrylate, and 75 g (15 mass%) of styrene. The weight average molecular weight of PA-4 measured by GPC in terms of polystyrene was 5.0 × 10 4 It was. [Synthesis Example 8] Production of copolymer (PA-5) A copolymer PA-5, which is component (C), was produced in the same manner as in Synthesis Example 4, except that the mixing ratio of the monomers to be dropped was 800 g (36 mass%) of dibutyl fumarate, 866 g (40 mass%) of styrene, and 525 g (24 mass%) of hydroxyethyl methacrylate. The weight average molecular weight of PA-5 measured by GPC in terms of polystyrene was 2.2 × 10 4 It was.
[0071] [Example 1] 10.6 parts by mass (solid content equivalent) of UA-1 produced in Synthesis Example 1 as component (A), 4.8 parts by mass of dipentaerythritol hexaacrylate (manufactured by Miwon, product name MIRAMER M600), 2.2 parts by mass of trimethylolpropane tetraacrylate (manufactured by Miwon, product name MIRAMER M300), 0.7 parts by mass of EO-modified hydrogenated bisphenol A diacrylate (manufactured by Miwon, product name MIRAMER M240), and 1.5 parts by mass of tetrahydroxyfurfuryl acrylate (manufactured by Miwon, product name MIRAMER M150) as component (B), 4.1 parts by mass (solid content equivalent) of PA-1 and 6.0 parts by mass (solid content equivalent) of PA-2 as component (C), 0.4 parts of 1-hydroxycyclohexyl phenyl ketone and 0.8 parts of benzophenone as component (D), and fluorine-containing group-, hydrophilic group-, and lipophilic group-containing oligomer (manufactured by DIC, product name MIRAMER M240) as additives. An active energy ray-curable composition (undercoat material) was produced by mixing and dissolving 0.1 parts by mass of Megafac F-477), 0.3 parts by mass of trismethacryloyloxyphosphate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name Viscoat 3PMA), and 30 parts of toluene, 30 parts of xylene, 30 parts of n-butanol, and 20 parts of ethyl acetate as organic solvents. The active energy ray curable composition (undercoat material) was evaluated for smoothness by the method described below, and test pieces were prepared to evaluate the initial adhesion and moisture resistance. The results are shown in Table 1.
[0072] [Evaluation of smoothness] The composition was spray-coated on an ABS substrate so that the film thickness after curing was 15 μm. The composition was then heated in an oven at 60° C. for 2 minutes to volatilize the organic solvent. After that, a high-pressure mercury lamp was used to irradiate the coating surface from above in air with an integrated light quantity of 1000 mJ / cm 2 . 2 After curing by irradiating with ultraviolet light (integrated ultraviolet energy amount of wavelength 340 nm to 380 nm), the appearance of the coating film was visually observed. Smoothness was evaluated according to the following criteria. ⊚: The surface is smooth and highly glossy. ◯: The surface is smooth, but the luster is somewhat dull. △: The surface is slightly uneven and not smooth. ×: The surface is very uneven and not smooth.
[0073] [Preparation of test pieces] 20 parts by mass of a toluene solution of PA-4 (10 parts by mass in terms of solid content), 30 parts by mass of dipentaerythritol hexaacrylate (manufactured by Miwon, product name MIRAMER M600), 20 parts by mass of trimethylolpropane triacrylate (manufactured by Miwon, product name MIRAMER M300), 25 parts by mass of EO-modified hydrogenated bisphenol A diacrylate (manufactured by Miwon, product name MIRAMER M240), 10 parts by mass of tetrahydrofurfuryl acrylate (manufactured by Osaka Organic Chemical Industry, product name: Viscoat #150), 5 parts by mass of benzophenone, 30 parts by mass of toluene, 30 parts by mass of xylene, 30 parts by mass of n-butanol, and 20 parts by mass of ethyl acetate were mixed and stirred to prepare a top coat material (1) (not corresponding to the active energy ray curable composition of the present invention). The active energy ray curable composition (undercoat material) for evaluation was spray-coated on a rectangular sheet made of ABS resin, 9 cm long, 5 cm wide, and 3 mm thick, so that the thickness of the cured coating film was 15 μm. The sheet was then heated in an oven at 60° C. for 2 minutes to volatilize the organic solvent. Thereafter, a high-pressure mercury lamp was used to irradiate the coating surface from above in air, with an integrated light dose of 1000 mJ / cm 2 . 2 The undercoat layer was then cured by irradiating it with ultraviolet light (integrated ultraviolet energy amount with a wavelength of 340 nm to 380 nm) to form an undercoat layer. Aluminum was then deposited on the surface of the undercoat layer by vacuum deposition, and a topcoat layer was formed under the same conditions as the undercoat layer using the above topcoat material (1) for the purpose of preventing corrosion of the metal film, etc., to prepare a laminate for evaluation (hereinafter referred to as a test piece).
[0074] [Evaluation of initial adhesion] Make cuts in a grid pattern with a cutter knife at 1mm intervals down to the base material on the test piece. 2A hundred grids were made, and Nichiban Cellotape (registered trademark) was applied on them and then quickly peeled off, and the state of the peeled grids between the substrate and undercoat, the undercoat and metal film, or the metal film and topcoat was observed. The initial adhesion was evaluated according to the following criteria. ◎...No peeling in checkerboard cut peel test. ◯: No peeling in the cross-cut test, but the cut grooves are slightly chipped. △: Slight peeling in the cross-cut test. ×...Complete peeling in checkerboard cut test.
[0075] [Moisture resistance evaluation] The test pieces were left in an atmosphere of 50℃ and 98% RH for 72 hours, then removed and visually inspected for appearance and rated according to the following criteria.Furthermore, testing and evaluation were performed in the same manner as for the initial adhesion test described above. (Appearance Evaluation Criteria) 〇…No abnormalities. △: The coating is slightly whitened. ×: Significant whitening of coating film.
[0076] [Example 2, Comparative Example 1] An active energy ray-curable composition (undercoat material) was prepared and evaluated in the same manner as in Example 1, except for using the blending and composition shown in the composition column in Table 1. The results are shown in Table 1.
[0077] [Example 3] An active energy ray curable composition (top coat material) was prepared in the same manner as in Example 1, except that the blending and composition were as shown in the composition column in Table 1. The smoothness of this active energy ray curable composition (undercoat material) was evaluated in the same manner as in Example 1. In addition, test pieces were prepared by the following method, and the initial adhesion and moisture resistance were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0078] [Preparation of test pieces] 12 parts by mass of a toluene solution of PA-5 (6 parts by mass in terms of solid content), 10 parts by mass of epoxy acrylate (Miwon, product name MIRAMER PE210), 5 parts by mass of polyester acrylate (Miwon, product name MIRAMER PS4140), 5 parts by mass of caprolactone-modified dipentaerythritol hexacrylate (Nippon Kayaku, product name: DPCA-20), 4 parts by mass of PO-modified neopentyl glycol diacrylate (Miwon, product name MIRAMER M216), 0.4 parts by mass of benzophenone, 0.8 parts by mass of 2,2-dimethoxy-2-phenylacetophenone, 30 parts by mass of toluene, 30 parts by mass of xylene, 30 parts by mass of n-butanol, and 20 parts by mass of ethyl acetate were mixed and stirred to prepare an active energy ray curable composition (2) (undercoat material, not applicable to the present invention). The active energy ray curable composition (2) (undercoat material) was spray-coated onto a rectangular sheet made of ABS resin, 9 cm long, 5 cm wide, and 3 mm thick, so that the thickness of the cured coating film was 15 μm. The sheet was then heated in an oven at 60° C. for 2 minutes to volatilize the organic solvent. After that, a high-pressure mercury lamp was used to irradiate the coated surface with an integrated light amount of 1000 mJ / cm in air from above the coated surface. 2 An undercoat layer was formed by irradiating the undercoat layer with ultraviolet light (integrated ultraviolet light energy of wavelength 340 nm to 380 nm) to form a cured coating film. Aluminum was then deposited on the surface of the undercoat layer by vacuum deposition, and a topcoat layer was formed under the same conditions as the undercoat layer using an active energy ray curable composition (topcoat material) for evaluation in order to prevent corrosion of the metal film, etc., to prepare a test piece.
[0079] [Example 4, Comparative Example 2] An active energy ray-curable composition (top coat material) was prepared and evaluated in the same manner as in Example 3, except that the blending and composition were as shown in the composition column in Table 1. The results are shown in Table 1.
[0080] [Table 1]
[0081] The abbreviations in Table 1 represent the following compounds. UA-1: Urethane acrylate UA-1 obtained in Synthesis Example 1 UA-2: Urethane acrylate UA-2 obtained in Synthesis Example 2 UA-3: Urethane acrylate UA-3 obtained in Synthesis Example 3 DPHA: Dipentaerythritol hexaacrylate (Miwon, product name: MIRAMER M600) PS4140: Polyester acrylate (Miwon, product name: MIRAMER PS4140) TMPTA: Trimethylolpropane tetraacrylate (Miwon, product name: Miramer M300) PETIA: Pentaerythritol tetraacrylate (Miwon, product name: Miramer M340) BPAEODA: EO2 mole modified bisphenol A diacrylate (Miwon, product name: Miramer M240) A-DOG: Dioxane glycol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: NK Ester A-DOG) THFA: Tetrahydroxyfurfuryl acrylate (Miwon, product name: Miramer M150) EHA: 2-Ethylhexyl acrylate (Mitsubishi Chemical) PA-1: Copolymer PA-1 obtained in Synthesis Example 4 PA-2: Copolymer PA-2 obtained in Synthesis Example 5 PA-3: Copolymer PA-3 obtained in Synthesis Example 6 PA-4: Copolymer PA-4 obtained in Synthesis Example 7 HCPK: 1-Hydroxycyclohexyl phenyl ketone BPN: Benzophenone ·MBF: Methyl benzoyl formate ·F-477: Oligomer containing fluorine-containing group, hydrophilic group, and lipophilic group (manufactured by DIC, product name: Megafac F-477) BYK-3440: Acrylic copolymer (manufactured by BYK, product name: BYK-3440) 3PMA: Trismethacryloyloxyphosphate (Osaka Organic Chemical Industry Co., Ltd., product name: Viscoat 3PMA) PM-21: 2-methacryloyloxyethyl caproate acid phosphate (manufactured by Nippon Kayaku Kogyo Co., Ltd., product name: Kayamar PM-21)
[0082] From the above examples, it can be seen that the cured coating film formed from the active energy ray-curable resin composition of the present invention was excellent in smoothness and moisture resistance. On the other hand, the cured coating film formed from the active energy ray-curable resin composition not containing component (A) had insufficient moisture resistance. [Industrial Applicability]
[0083] The active energy ray-curable resin composition of the present invention can form a cured coating film having excellent moisture resistance and smoothness, and therefore can be suitably used as a material for an undercoat layer or a topcoat layer when forming a metal film on the surface of a substrate by a metallization treatment such as ionization deposition or sputtering.
Claims
1. An active energy ray-curable resin composition comprising: a urethane (meth)acrylate (A) having a structure derived from the following compound (a1); a monomer (B) other than the component (A) having at least one (meth)acryloyl group; a (co)polymer (C) of a vinyl-based monomer; and a photopolymerization initiator (D). Compound (a1): at least one polyol selected from the following compound (a12): Compound (a12): Polyester polyol obtained from sebacic acid and polyol
2. The active energy ray-curable resin composition according to claim 1, wherein the urethane (meth)acrylate (A) is a urethane (meth)acrylate obtained by reacting the compound (a1), the following compound (a2), and the following compound (a3): Compound (a2): Isocyanate having at least two isocyanate groups Compound (a3): Compound having a hydroxyl group and a (meth)acryloyloxy group
3. 3. The active energy ray curable resin composition according to claim 1, wherein the amount of the component (A) is 5 to 50 mass%, the amount of the component (B) is 20 to 80 mass%, and the amount of the component (C) is 1 to 30 mass%, based on the total amount of the components (A) to (C).
4. A cured product obtained by curing the active energy ray-curable resin composition according to any one of claims 1 to 3 by irradiating it with active energy rays.
5. A laminate having a cured coating film comprising the cured product according to claim 4 on the surface of a substrate.
6. 6. The laminate according to claim 5, comprising a substrate, a cured coating film comprising the cured product according to claim 4, and a metal film laminated in this order.
7. The laminate according to claim 6, further comprising a cured coating film laminated on the surface of the metal film.
Citation Information
Patent Citations
Fingerprint identification paint and preparing method and application thereof
CN106189803A
Photocurable resin composition
JP2000026555A
Tile sheet and method of manufacturing the same
JP2011047153A
Undercoat layer-forming coating material composition for metal deposition and resin molded product
JP2011140554A
Ultraviolet-curable resin composition
JP2012077273A